-6t-8=9t=

Simple and best practice solution for -6t-8=9t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6t-8=9t= equation:



-6t-8=9t=
We move all terms to the left:
-6t-8-(9t)=0
We add all the numbers together, and all the variables
-15t-8=0
We move all terms containing t to the left, all other terms to the right
-15t=8
t=8/-15
t=-8/15

See similar equations:

| -6t-8=9 | | 56=u/5+47 | | 36x/x=1550 | | 36x/x= | | 10x^2+10=90 | | X2+4x-218=0 | | (4x-1)⋮=(2x-1) | | m/4+16=12 | | 48=-4x+8 | | c/4+10=7 | | 6=-2+-2t | | 48=4f | | 10t−-14=94 | | (X+18)=(2x-28) | | 5.1.b=-7.1 | | 34(x−13)=−2(9+x) | | 8a=7a+13 | | -4-10t=94 | | 3a=56579956 | | 8a=7a=13 | | 4x-5+9x-9=180 | | -3p+-1=8 | | 16=2w-14 | | 4=6+v/2 | | a=15=15 | | 6(y-94)=30 | | -9(g+62)=-18 | | k/2+2=4 | | 40=8(s+1) | | t/4+4=0 | | -26=g/9-30 | | 2s+-1=1 |

Equations solver categories